PENERAPAN MODEL PEMBELAJARAN KOOPERATIF ROTATING TRIO EXCHANGE (RTE) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROLISIS GARAM DI KELAS XI IPA SMA N 9 PEKANBARU - Astuti, Rini; Erna, Maria; ', Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The implementation of cooperative learning model Rotating Trio Exchange (RTE) has been conducted to determine the improve in student achievement and improve learning achievement category on the subject of salt hydrolysis in class XI SMA N 9 Pekanbaru. Forms of this research is experimental research design with pretest - posttest. Time data collection between February 8 to April 13, 2016. The sample consisted of two classes, grade XI IPA 3 as the control class and class XI IPA 5 as an experimental class selected at random. Grades given experimental treatment with the application of Rotating Trio Exchange (RTE), while the control class are given learning lecture method. Data analysis technique used is the t-test. Based on the analysis of data processing obtained t¬hitung> ttable is 4.94> 1.67 means that the implementation of cooperative learning model Rotating Trio Exchange (RTE) can improve student achievement on the subject of salt hydrolysis in class XI SMA N 9 Pekanbaru. Category increase student achievement in the classroom experiment with a normalized gain value (N-gain) of 0.91 is included in the high category.Keywords: Rotating Trio Cooperative Exchange (RTE), Achievement, Hydrolysis Salt